How do you find exponential decay rate?
Answer
Verified
444k+ views
Hint:Here in this question we have to find the exponential decay rate. That is, the rate at which a population of something decays is directly proportional to the negative of the current population at time t. So we can introduce a proportionality constant. Then further applying an integration on both sides and on simplification we get the required result.
Complete step by step answer:
Exponential decay describes the process of reducing an amount by a consistent percentage rate over a period of time. It can be expressed by the formula \[y = a{\left( {1 - b} \right)^x}\] where y is the final amount, a is the original amount, b is the decay factor, and x is the amount of time that has passed. Exponential decays typically start with a differential equation of the form:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}}\alpha \, - N(t)\]
That is, the rate at which a population of something decays is directly proportional to the negative of the current population at time t. So we can introduce a proportionality constant \[\alpha \]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}} = - \alpha \,N(t)\]
We will now solve the equation to find a function of \[N(t)\]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{N(t)}} = - \alpha \,dt\]
\[ \Rightarrow \,\,\dfrac{{dN}}{N} = - \alpha \,dt\]
Apply integration both sides, then
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = \int { - \alpha } \,dt\]
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = - \alpha \int {dt} \,\]
Using the integration formula \[\int {\dfrac{1}{x}dx = \ln x + c} \] and \[\int {dx = x + c} \], where c is an integrating constant.
\[ \Rightarrow \,\,\ln N = - \alpha t + c\,\]
As we know the logarithm function is the inverse form of exponential function, then
\[ \Rightarrow \,\,N = {e^{ - \alpha \,\,t + c}}\,\]
Or it can be written as:
\[ \therefore \,\,N = A{e^{ - \alpha \,t}}\]
Where A is a constant.
Hence, the general form of exponential decay rate is \[N = A{e^{ - \alpha \,t}}\].
Note:Exponential decay describes the process of reducing an amount by a constant percentage rate over a period of time. The integration is inverse of the differentiation so to cancel differentiation the integration is applied. Likewise the logarithm is inverse of exponential. Hence by using these concepts we obtain answers.
Complete step by step answer:
Exponential decay describes the process of reducing an amount by a consistent percentage rate over a period of time. It can be expressed by the formula \[y = a{\left( {1 - b} \right)^x}\] where y is the final amount, a is the original amount, b is the decay factor, and x is the amount of time that has passed. Exponential decays typically start with a differential equation of the form:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}}\alpha \, - N(t)\]
That is, the rate at which a population of something decays is directly proportional to the negative of the current population at time t. So we can introduce a proportionality constant \[\alpha \]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{dt}} = - \alpha \,N(t)\]
We will now solve the equation to find a function of \[N(t)\]:
\[ \Rightarrow \,\,\dfrac{{dN}}{{N(t)}} = - \alpha \,dt\]
\[ \Rightarrow \,\,\dfrac{{dN}}{N} = - \alpha \,dt\]
Apply integration both sides, then
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = \int { - \alpha } \,dt\]
\[ \Rightarrow \,\,\int {\dfrac{{dN}}{N}} = - \alpha \int {dt} \,\]
Using the integration formula \[\int {\dfrac{1}{x}dx = \ln x + c} \] and \[\int {dx = x + c} \], where c is an integrating constant.
\[ \Rightarrow \,\,\ln N = - \alpha t + c\,\]
As we know the logarithm function is the inverse form of exponential function, then
\[ \Rightarrow \,\,N = {e^{ - \alpha \,\,t + c}}\,\]
Or it can be written as:
\[ \therefore \,\,N = A{e^{ - \alpha \,t}}\]
Where A is a constant.
Hence, the general form of exponential decay rate is \[N = A{e^{ - \alpha \,t}}\].
Note:Exponential decay describes the process of reducing an amount by a constant percentage rate over a period of time. The integration is inverse of the differentiation so to cancel differentiation the integration is applied. Likewise the logarithm is inverse of exponential. Hence by using these concepts we obtain answers.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE